PENGARUH PENERAPAN E-SYSTEM PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA KEPANJEN - Isro’i Isro’i; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2018)
AbstractThis study was conducted to determine the effect of e-systemimplementation (e-registration, e-SPT, e-billing and e-filling) taxation ontaxpayer compliance level in Tax Service Office (KPP) Pratama Kepanjen. Thetype of this research is correlation research and using primary data source bydistributing questionnaire of 120 questionnaires to individual taxpayer asrespondent. The technique used in data retrieval is incdental sampling while thedata analysis techniques use multiple linear regression analysis assisted withSPSS program.The result of partial research shows that the application of e-registration,e-SPT, e-billing and e-filling have a positive and significant effect on the taxpayercompliance level of the individual while the research result simultaneously showsthat the application of all e-system have positive effect on the level of complianceindividual taxpayer.Keywords: e-Registration, e-SPT, e-Billing, e-Filling, Taxpayer compliance